Metagenomic sequencing identified microbial species in the rumen and cecum microbiome responsible for niacin treatment and related to intramuscular fat content in finishing cattle - Yang, Zhuqing; Chen, Xiao; Yu, Mingjin; Jing, Ruixue; Bao, Linbin; Zhao, Xianghui; Pan, Ke; Chao, Bihui; Qu, Mingren (Frontiers in Microbiology, 2024)
Niacin is one of the essential vitamins for mammals. It plays important roles in maintaining rumen microecological homeostasis. Our previous study indicated that dietary niacin significantly elevated intramuscular fat content (IMF) in castrated finishing steers. Whether niacin affects fat deposition by regulating the microbial composition and functional capacities of gastrointestinal microbiome has been unknown yet. In this study, 16 castrated Xiangzhong Black cattle were randomly assigned into either control group fed with a basal concentrate diet (n = 8) or niacin group fed with a basal concentrate diet added 1000 mg/kg niacin (n = 8). Seven rumen samples and five cecum content samples were randomly collected from each of control and niacin groups for metagenomic sequencing analysis. A total of 2,981,786 non-redundant microbial genes were obtained from all tested samples. Based on this, the phylogenetic compositions of the rumen and cecum microbiome were characterized. We found that bacteria dominated the rumen and cecum microbiome. Prevotella ruminicola and Ruminococcus flavefaciens were the most abundant bacterial species in the rumen microbiome, while Clostridiales bacterium and Eubacterium rectale were predominant bacterial species in the cecum microbiome. Rumen microbiome had significantly higher abundances of GHs, GTs, and PLs, while cecum microbiome was enriched by CBMs and AAs. We found a significant effect of dietary niacin on rumen microbiome, but not on cecum microbiome. Dietary niacin up-regulated the abundances of bacterial species producing lactic acid and butyrate, fermenting lactic acid, and participating in lipid hydrolysis, and degradation and assimilation of nitrogen-containing compounds, but down-regulated the abundances of several pathogens and bacterial species involved in the metabolism of proteins and peptides, and methane emissions. From the correlation analysis, we suggested that niacin improved nutrient digestion and absorption, but reduced energy loss, and Valine, leucine and isoleucine degradation of rumen microbiome, which resulted in the increased host IMF. The results suggested that dietary manipulation, such as the supplementation of niacin, should be regarded as the effective and convenient way to improve IMF of castrated finishing steers by regulating rumen microbiome.